Kisah Cinta Platonik Jalâl al-Dîn al-Rûmî - Zayyin Alfi Jihad (Department of Aqidah and Islamic Philosophy, Faculty of Ushuluddin and Philosophy, Sunan Ampel State Islamic University Surabaya, 2011)
The research attempts to discover and find the very roots of the love concept by Jalâl al-Dîn Rûmî to develop the Sufism method, which connects human’s hearts with their God. This study employs a philosophical qualitative method, which tends to be descriptive and interpretative. Using the basis of love, Jalâl al-Dîn Rûmî built a Sufistic epistemological foundation in the form of mystical poems. Poems are a means of spiritual pilgrimage, which is performed to find the culmination of fusion ecstasy between humans and their God, i.e., Allah The Almighty.